3‐D Regional Ionosphere Imaging and SED Reconstruction With a New TEC‐Based Ionospheric Data Assimilation System (TIDAS) - Ercha Aa; Shun‐Rong Zhang; Philip J. Erickson; Wenbin Wang; Anthea J. Coster; William Rideout (Space Weather)
Abstract A new TEC‐based ionospheric data assimilation system (TIDAS) over the continental US and adjacent area (20°–60°N, 60°–130°W, and 100–600 km) has been developed through assimilating heterogeneous ionospheric data, including dense ground‐based Global Navigation Satellite System (GNSS) Total Electron Content (TEC) from 2,000+ receivers, Constellation Observing System for Meteorology, Ionosphere, and Climate radio occultation data, JASON satellite altimeter TEC, and Millstone Hill incoherent scatter radar measurements. A hybrid Ensemble‐Variational scheme is utilized to reconstruct the regional 3‐D electron density distribution: a more realistic and location‐dependent background error covariance matrix is calculated from an ensemble of corrected NeQuick outputs, and a three‐dimensional variational (3DVAR) method is adopted for measurement updates to obtain an optimal state estimation. The spatial‐temporal resolution of the reanalyzed 3‐D electron density product is as high as 1° × 1° in latitude and longitude, 20 km in altitude, and 5 min in universal time, which is sufficient to reproduce ionospheric fine structure and storm‐time disturbances. The accuracy and reliability of data assimilation results are validated using ionosonde and other measurements. TIDAS reanalyzed electron density is able to successfully reconstruct the 3‐D morphology and dynamic evolution of the storm‐enhanced density (SED) plume observed during the St. Patrick's day geomagnetic storm on 17 March 2013 with high fidelity. Using TIDAS, we found that the 3‐D SED plume manifests as a ridge‐like high‐density channel that predominantly occurred between 300 and 500 km during 19:00–21:00 UT for this event, with the F2 region peak height being raised by 40–60 km and peak density enhancement of 30%–50%.